2009
DOI: 10.1111/j.1360-0443.2008.02448.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated high‐frequency transcranial magnetic stimulation over the dorsolateral prefrontal cortex reduces cigarette craving and consumption

Abstract: Multiple high-frequency rTMS of the DLPFC can attenuate nicotine craving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
190
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(210 citation statements)
references
References 48 publications
(56 reference statements)
11
190
0
9
Order By: Relevance
“…Although DA-containing neurons are located deeply in the brainstem, making them inaccessible to direct rTMS stimuli, DA neurons may be reached indirectly through neurons located elsewhere in the brain. For example, the dorsolateral prefrontal cortex (DLPfcx), the brain region targeted in many rTMS studies (eg, Amiaz et al, 2009), projects monosynaptically to the VTA, which contains the cell bodies of DA-producing cells (Carr and Sesack, 2010). Indeed, these cortical neurons could be 'used' as the primary target of the rTMS stimulus to produce, ultimately, an increase in DA availability in the synaptic cleft in the Nacc.…”
Section: Future Research Directions: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Although DA-containing neurons are located deeply in the brainstem, making them inaccessible to direct rTMS stimuli, DA neurons may be reached indirectly through neurons located elsewhere in the brain. For example, the dorsolateral prefrontal cortex (DLPfcx), the brain region targeted in many rTMS studies (eg, Amiaz et al, 2009), projects monosynaptically to the VTA, which contains the cell bodies of DA-producing cells (Carr and Sesack, 2010). Indeed, these cortical neurons could be 'used' as the primary target of the rTMS stimulus to produce, ultimately, an increase in DA availability in the synaptic cleft in the Nacc.…”
Section: Future Research Directions: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Although no difference in craving was found, the results illustrated an advantage of TMS in smoking cessation [28]. Meanwhile, Johann et al demonstrated that rTMS can also reduce cigarette craving [29]; this effect was replicated in a subsequent study using a more rigorous experimental design and a larger group of participants [30]. This study demonstrated that rTMS over the dlPFC reduces both cigarette consumption and craving, though the effects were not robust and seemed to dissipate over time [30].…”
Section: Evidence Supporting Tms As a Treatmentmentioning
confidence: 76%
“…Meanwhile, Johann et al demonstrated that rTMS can also reduce cigarette craving [29]; this effect was replicated in a subsequent study using a more rigorous experimental design and a larger group of participants [30]. This study demonstrated that rTMS over the dlPFC reduces both cigarette consumption and craving, though the effects were not robust and seemed to dissipate over time [30]. Furthermore, rTMS may serve as an additional aid in cognitive-behavioral therapy for intermediate nicotine abstinence [31].…”
Section: Evidence Supporting Tms As a Treatmentmentioning
confidence: 78%
“…In addition, studies successfully employing brain stimulation of the prefrontal cortex as treatment in nicotine dependent individuals further argues for the role of plasticity executive function across nicotine addiction and recovery [33,34].…”
Section: Journal Of Addiction Research and Therapymentioning
confidence: 99%